1997
DOI: 10.1002/(sici)1098-2280(1997)30:2<147::aid-em7>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage in leukocytes and buccal and nasal epithelial cells of individuals exposed to air pollution in Mexico City

Abstract: There is an increased interest in using biological markers to monitor individuals for possible exposure to environmental toxicants. Test systems which permit the sensitive detection of DNA damage and DNA repair are critically important in such studies. The single cell gel electrophoresis (SCG) assay is a rapid and a sensitive method for the evaluation of DNA damage at the single cell level, providing information on the occurrence of DNA single-strand breaks and alkali labile sites using alkaline conditions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The findings of our study indicate that buccal epithelial cells could also be used for evaluating the topically applied mouthrinse. The present study confirmed the results of other studies in which buccal cells were used for cytogenetic evaluation [18,21,29].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of our study indicate that buccal epithelial cells could also be used for evaluating the topically applied mouthrinse. The present study confirmed the results of other studies in which buccal cells were used for cytogenetic evaluation [18,21,29].…”
Section: Discussionsupporting
confidence: 91%
“…Several other cytogenetic techniques such as sister chromatid exchange (SCE), chromosomal aberration, and micronuclei assay have been used to evaluate the type and degree of such mutagenic behavior at a chromosomal level . The single-cell gel electrophoresis (SCGE), or comet assay, has also been used in similar studies [Calderon-Garciduenas et al, 1997;Valverde et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Calderón-Garcidueñas et al, 1996;Valverde et al, 1997) have demonstrated an increase in DNA damage in nasal epithelial cells of people exposed to urban air pollution. Ozone and NO 2 are the major oxidants that coexist in photochemical smog.…”
Section: Discussionmentioning
confidence: 99%